The Effect of Interactive Book Ceria to Improve Listening Skills of 5 to 6-Year-Old Children at TK PG Lab FKIP Universitas Riau - Resy Nur Aisya Adma; Chairilsyah, Daviq; Risma, Devi (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
This study aims to analyse the effect of the interactive book CERIA on the listening skills of children aged 5-6 years at TK PG LAB FKIP Universitas Riau. The research background is the children’s low listening skills, especially in paying attention, understanding the content, and the ability to repeat and answer questions from the story. The research used a one-group pretest-posttest experimental design with 16 children as subjects. Data were collected through observation and analysed using the t-test and N-Gain calculation. The results reveal a significant increase in listening skills after treatment, with a t value of 20.708 and a significance of 0.000 (p <0.05). The N-Gain value reveals an effectiveness of 53.88%. These results indicate that the interactive book CERIA is effective as an innovative learning medium to improve the listening skills of early childhood children.